Las finanzas municipales chilenas: 1833-1887 - Nazer Ahumada, Juan Ricardo (Historia, 1999)
<span style="color: #111111; font-family: ’Trebuchet MS’, ’Lucida Grande’, Lucida, Verdana, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Chilean municipalities during the 19th century were completely dependent on the government and constantly short of funds. The Constitution of 1833 contemplated municipalities which embraced large territories and various urban centers. The capital of the Department was the seat of the municipality which was under the authority of the local governor. In these conditions, municipal finances were dependent on decisions taken in Santiago. Originally the municipalities relied on the colonial system of revenues to which were added a series of local taxes on commerce, street lighting and urban transpon, with poor results. In the middle of the century, the central government provided a new financial structure based on local imposts, state subsidies and the possibility of borrowing for public works. Although municipal finances improved, sustained borrowing, especially in the large cities, led to a crisis towards 1880, when some municipalities were assigning upto 50 percent of ther income to service debts. The problem was solved thanks to the income from nitrate which allowed for the payment of the municipal debts and a complete overhaul of the municipal system known as the "Comuna Autónoma".